Continuous veno‐venous hemofiltration for severe acute pancreatitis - Lin, Yanjun (Cochrane Database Syst Rev, 2019)
BACKGROUND: Severe acute pancreatitis is associated with high rates of mortality and life‐threatening complications. Continuous veno‐venous hemofiltration (CVVH) has been used in some centers to reduce mortality and avoid local or systemic complications; however, its efficacy and safety are uncertain. OBJECTIVES: To assess the benefits and harms of CVVH in patients suffering from severe acute pancreatitis; to compare the effects of different CVVH techniques; and to evaluate the optimal time for delivery of CVVH. SEARCH METHODS: We searched the Cochrane Library (2019, Issue 8), MEDLINE (1946 to 13 September 2019), Embase (1974 to 13 September 2019), and Science Citation Index Expanded (1982 to 13 September 2019). SELECTION CRITERIA: We included all randomized controlled trials (RCTs) that compared CVVH versus no CVVH in participants with severe acute pancreatitis. We also included RCTs that compared different types of CVVH and different schedules for CVVH in participants with severe acute pancreatitis. DATA COLLECTION AND ANALYSIS: Two review authors independently identified the trials for inclusion, collected the data, and assessed the risk of bias. We performed the meta‐analyses using Review Manager 5. We calculated the risk ratio (RR) for dichotomous outcomes, and the mean difference (MD) for continuous outcomes, with 95% confidence intervals (CIs). We used GRADE to assess the certainty of the evidence for all outcomes. MAIN RESULTS: We included three RCTs, involving a total of 219 adults with severe acute pancreatitis with various etiologies, including alcoholic abuse, biliary disease, high‐fat diet, hyperlipidemia, etc. All of the participants had single or multiple organ failure. All of the RCTs were single‐center studies conducted in China. The mean age of participants was 47.4 years. The mean proportion of females was 42.0%. All RCTs were at high risk of bias. CVVH versus no CVVH We included two RCTs in which 189 participants with severe acute pancreatitis were randomized to undergo CVVH (97 participants) or no CVVH (92 participants). The evidence is very uncertain about the effect of CVVH on in‐hospital mortality (RR 0.62, 95% CI 0.27 to 1.40; 2 studies, 189 participants; very low‐certainty evidence) compared with no CVVH. The evidence suggests that CVVH may reduce length of stay in the intensive care unit (ICU) (MD ‐8.80 days, 95% CI ‐10.24 to ‐7.36 days; 1 study, 125 participants; very low‐certainty evidence), length of hospital stay (MD ‐26.40 days, 95% CI ‐30.17 to ‐22.63 days; 1 study, 125 participants; very low‐certainty evidence), and total hospital cost (MD ‐2800.00 dollars, 95% CI ‐3881.74 to ‐1718.26 dollars; 1 study, 125 participants; very low‐certainty evidence) compared with no CVVH but the evidence is very uncertain. Adverse events and quality of life were not reported in the studies. One type ofCVVH versus a different type of CVVH We included one RCT in which 30 participants with severe acute pancreatitis were randomized to undergo high‐volume CVVH (15 participants) or standard CVVH (15 participants). High‐volume CVVH may result in little to no difference in in‐hospital mortality compared with standard CVVH (RR 0.60, 95% CI 0.17 to 2.07; 1 study, 30 participants; low‐certainty evidence). The evidence is very uncertain about the effect of high‐volume CVVH on adverse events compared with standard CVVH (RR 1.00, 95% CI 0.16 to 6.20; 1 study, 30 participants; very low‐certainty evidence). Length of ICU stay, length of hospital stay, total hospital cost, and quality of life were not reported in the study. AUTHORS' CONCLUSIONS: The certainty of the current evidence is very low or low. For both comparisons addressed in this review, data are sparse. The evidence is very uncertain about the effect of CVVH on mortality in patients with severe acute pancreatitis. Very low‐certainty evidence suggests CVVH may reduce length of ICU stay, length of hospital stay, and total hospital cost but the evidence is very uncertain. The evidence is also very uncertain whether high‐volume CVVH is superior, equivalent or inferior to standard CVVH in patients with severe acute pancreatitis.